Application of Electrospray Coating Technique to impart Multifunctionality to Textile Substrates (Journal of Fiber Bioengineering and Informatics, 2016)
Electrospray coating is a method of generating fine droplets of polymer through high electrostaticcharging. It involves electrohydrodynamic process for forming fine polymer droplets. These droplets arehighly charged that promotes self-dispersion which results in uniform coating on substrate. Electrospraycoating can be successfully utilised as a coating technique to coat textile substrates. Textiles substratecoated with electrosprayed polymer droplets have a large specific surface area and it facilitates submicronrange coating compared to conventional coating methods like roller coating or knife coating. Thisresearch study investigates the electrospray coating of thermoplastic polyurethane polymer on textilesubstrate. The results showed that electrospraying facilitated the submicron size droplets deposition ontextile substrates which imparted the waterproof property to the substrate without altering the moisturemanagement and surface properties of textile substrate.